Waste Oil Processing to Soap Bar With Extract of Turmeric, Aloe vera , and Papaya - Julianto Wijaya; Ainun Rohana; Adian Rindang (Universitas Sumatera Utara, 2014)
Waste Oil is the remains of frying oil that can not be reused. Therefore further processing is needed, one of them is being bar soap. The study was aimed to use waste oil into bar soap with extract of turmeric, aloe vera and papaya. The study was conducted at the Laboratory of Agricultural Engineering and Analysis of was done in Food Chemical Analysis Laboratorium Faculty of Agricultural in May 2014 to July 2014 by using a non-factorial completely randomized design. Parameters measured were water content, free fatty acid(FFA), alcohol insoluble part, and organoleptic test. The results show that turmeric, aloe vera, and papaya extract had no significant effect on water content, free fatty acid(FFA) and alcohol insoluble part. Keywords: Aloe vera, bar soap ,papaya, turmeric, waste oil